Influence Of Location On Patient Satisfaction In The Technical Implementation Unit Of Puskesmas Simalingkar Medan - Devi Irawati Tinambunan (JURNAL ILMIAH SOCIO SECRETUM, 2023)
Location is a place of service, related to where the company must be headquartered and carry out its operations or activities. While patient satisfaction is a level of patient feelings that arise as a result of the performance of health services obtained after the patient compares with what is felt. The formulation of the problem that the author wants to know is "Does Location affect Patient Satisfaction at the Technical Implementation Unit of the Medan Simalingkar Health Center?''. The framework of thinking in this research consists of two variables, namely: Variable X (Location) and Variable Y (Patient Satisfaction). The population in this study were a number of patients using outpatient services at the Simalingkar Health Center Medan. The sample amounted to 79 respondents and the data collection techniques in this study were a list of questions (questionnaires) and interviews. The data analysis technique used is simple linear regression analysis using SPSS 22 Windows. The equation form of this analysis is Y= a+bX+e, after the data is analyzed with the help of SPSS, the regression equation obtained is: Y= 12.198+0.572 X based on the results of the coefficient of determination R^2, the R Square value is 0.59.0 . The results of the statistical test (t test), obtained a value of tcount > ttable (4.797>1.991) with a significance level (0.000 <0.05), so it can be concluded that the results in this study are the location has a significant effect on patient satisfaction in the Technical Implementation Unit of the Puskesmas Simalingkar Medan. It is recommended that the Simalingkar Medan Health Center further improve the location strategy in order to achieve patient satisfaction.